オーロラ カンソクヨウ レーダ ソウチ オヨビ ショウワキチ ニ オケル レーダ オーロラ ノ シュツゲン トクセイ - 長谷川, 貞雄; ハセガワ, サダオ; 城, 功; シロ, イサオ; 大瀬, 正美; オオセ, マサミ; 竹内, 鉄雄; タケウチ, テツオ; 西牟田, 一三; ニシムタ, イチゾウ; HASEGAWA, Sadao; SHIRO, Isao; et al. (国立極地研究所, 1970)
P(論文) The observation of aurora by the radar method was carried out at Syowa Station in Antarctica during a period from April 1966 to December 1967. Instrumental outline and characteristics of the radio aurora are discussed in this paper. Results of this analysis are as follows : 1. The diurnal variation of the auroral echo occurrence takes a pronounced maximum in the morning (0300-0900L. T.) and a small maximum in the evening (1800-2200L. T.). 2. The seasonal variations of the echo activities were not distinct, but the minimum of the echo occurrence can be found only in the summertime in Antatctica. 3. On the oblique auroral reflections, the azimuthal distribution of the auroral echo occurrences showed that more auroral echoes are received from the region between 120° and 240°. 4. The occurrence time of the auroral echoes in all directions was about 0330L. T. in June, 0630L. T. in September and 0830L. T. in December. 5. The range of a maximum reception of the auroral echoes was about 300km, and the echoes from the outside region of 200km-1000km were not obtained. departmental bulletin paper